2023
DOI: 10.1101/2023.12.26.23300539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Theoretical Models to Practical Deployment: A Perspective and Case Study of Opportunities and Challenges in AI-driven Cardiac Auscultation Research for Low-Income Settings

Felix Krones,
Benjamin Walker

Abstract: This paper critically explores the opportunities and challenges of deploying Artificial Intelligence (AI) in healthcare. This study has two parallel components: (1) A narrative literature summary, which assesses the capacity of AI to aid in addressing the observed disparity in healthcare between high- and low-income countries. Despite the development of machine learning models for a wide range of diseases, many are never deployed in practice. We highlight various challenges that contribute to the lack of deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
(169 reference statements)
0
0
0
Order By: Relevance
“…The study found the system valuable and feasible, but also identified implementation issues, highlighting the challenges in integrating digital health solutions into existing healthcare models. Krones and Walker (2023) discuss the deployment of AI in healthcare, particularly in lowincome settings, through a case study on heart murmur detection in rural Brazil. Their Binary Bayesian ResNet model, which integrates patient heart sound recordings with demographic data, faced challenges in generalizing to out-of-distribution data.…”
Section: Case Studies: Success Stories and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found the system valuable and feasible, but also identified implementation issues, highlighting the challenges in integrating digital health solutions into existing healthcare models. Krones and Walker (2023) discuss the deployment of AI in healthcare, particularly in lowincome settings, through a case study on heart murmur detection in rural Brazil. Their Binary Bayesian ResNet model, which integrates patient heart sound recordings with demographic data, faced challenges in generalizing to out-of-distribution data.…”
Section: Case Studies: Success Stories and Limitationsmentioning
confidence: 99%
“…AI in healthcare presents a landscape of opportunities and challenges. The case studies by Perry et al (2021), Krones andWalker (2023), andFirouzi et al (2022) provide valuable insights into the practical applications of AI in healthcare, highlighting both its transformative potential and the hurdles that need to be overcome. As AI continues to evolve, addressing these challenges will be crucial for maximizing its benefits in improving healthcare outcomes.…”
Section: Case Studies: Success Stories and Limitationsmentioning
confidence: 99%